Pendekatan Dalam Pembelajaran Perspektif Imam Al Ghazali Dalam Kitab Ayyuhal Walad - Khoirun Nasihin (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2022)
The research method used is library research method. In addition, other supporting methods are historical methods, correlational methods and developmental methods. Then the data were analyzed using the method of content analysis (content analysis). The approach in learning the perspective of Imam Al Ghazali in the book of Ayyuhal Walad is an approach with theocentric nuances. This is shown by learning that has value is to get closer to Allah, the motivation in learning must be for the sake of reviving the Prophet's Shari'a and subjugating the lusts, students must maintain the sanctity of their souls, and practice the knowledge they have gained. The factors that determine success in learning the perspective of Imam Al Ghazali in the book Ayyuhal Walad are motivation, curriculum, educators, student and social environment